An integrated framework of plant form and function: the belowground perspective. Issue 1 (30th July 2021) - Weigelt, Alexandra; Mommer, Liesje; Andraczek, Karl; Iversen, Colleen M.; Bergmann, Joana; Bruelheide, Helge; Fan, Ying; Freschet, Grégoire T.; Guerrero‐Ramírez, Nathaly R.; Kattge, Jens; Kuyper, Thom W.; Laughlin, Daniel C.; et al.
Summary: Plant trait variation drives plant function, community composition and ecosystem processes. However, our current understanding of trait variation disproportionately relies on aboveground observations. Here we integrate root traits into the global framework of plant form and function. We developed and tested an overarching conceptual framework that integrates two recently identified root trait gradients with a well‐established aboveground plant trait framework. We confronted our novel framework with published relationships between above‐ and belowground trait analogues and with multivariate analyses of above‐ and belowground traits of 2510 species. Our traits represent the leaf and root conservation gradients (specific leaf area, leaf and root nitrogen concentration, and root tissue density), the root collaboration gradient (root diameter and specific root length) and the plant size gradient (plant height and rooting depth). We found that an integrated, whole‐plant trait space required as much as four axes. The two main axes represented the fast–slow 'conservation' gradient on which leaf and fine‐root traits were well aligned, and the 'collaboration' gradient in roots. The two additional axes were separate, orthogonal plant size axes for height and rooting depth. This perspective on the multidimensional nature of plant trait variation better encompasses plant function and influence on the surrounding environment.